THE EFFICIENCY OF DEVELOPING EXPLOSIVE STRENGTH AT THE INITIAL TRAINING STAGE IN THE SPORT OF WEIGHTLIFTING (Universal International Scientific Journal, 2026)
This article scientifically substantiates the effectiveness of explosive strengthdevelopment in young weightlifters at the initial training stage. Special speed-strength exercises,plyometric methods, and technical weightlifting movements were applied during the study. Theexperimental results demonstrated that targeted development of explosive strength significantlyimproves technical preparedness and competitive performance. Scientifically based planning of thetraining process at the initial stage is an essential factor in achieving high sports results.
Keywords: weightlifting; basic training; explosive power,